Design of a fluorescence technique using double laser pulse excitation for the measurement of molecular Brownian dynamics - Marconi, Mario Carlo, author; Etcheverry, J. I., author; Torga, J. R., author; Elsevier Science B. V., publisher (Colorado State University. Libraries, 1997)
A complete analysis of a novel method to evaluate the rotational diffusion time of fluorescent molecules is presented. It is based on the study of the total fluorescence produced after excitation with two consecutive short laser pulses. Expressions for the total fluorescence energy emitted in this case are derived, which would allow the evaluation of the rotational diffusion time. The main advantages of the proposed method are its simple setup, a time resolution only limited by the exciting laser pulsewidth, and the fact that it does not require fast time response detectors.
Keywords: Brownian dynamics; fluorescence anisotropy; rotational depolarization